MICROMECHANICAL APPROACH TO STRENGTH AND FRACTURE ANALYSIS OF HETEROGENEOUS MATERIALS - Bozorov Nosirjon Sodikovich; Umurkulov Kayumjon Parpievich; Alisherov Otabek Alisher ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article outlines the main regularities of the macromechanical approach to the analysis of the destruction of heterogeneous materials, it is also shown that the predictive capabilities of the various proposed theories of the destruction of composite materials.